2023
DOI: 10.1117/1.jrs.17.034512
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the influence of design and location on the cool island effect of the urban parks of Barcelona

Alan García-Haro,
Blanca Arellano,
Josep Roca

Abstract: .The aim of this research is to analyze the influence of park design and location on their cooling effect during summer daytime in Barcelona. Spatial analytical methods, utilizing the land surface temperature data from the Landsat 8 satellite, were employed to assess the intensity and spatial extent of the Park Cool Island (PCI) in 86 parks over four consecutive years. The study investigated the influence of factors such as the proportion of green land cover, park shape, and surrounding characteristics on thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
2
0
2
Order By: Relevance
“…En el cual, durante el momento de la medición las superficies se encontraban expuestas a la radiación solar directa, no obstante, por su ubicación al oeste de la edificación, en horas previas estos espacios se encontraban cubiertos por la sombra de la edificación, lo que se manifestó en una menor temperatura que el resto de espacios con las mismas características físicas, pero con distinta ubicación. No obstante, el beneficio microclimático de esta característica física de los espacios exteriores, es que su efecto se concentra en las proximidades de la edificación, cuya propagación hacia el entorno urbano, se ve limitada por el efecto de calentamiento causado por la configuración de las vialidades y otros espacios edificados cercanos (García- Haro, Arellano, & Roca, 2023).…”
Section: Disposición De Edificaciones Para La Reducción De La Inciden...unclassified
See 1 more Smart Citation
“…En el cual, durante el momento de la medición las superficies se encontraban expuestas a la radiación solar directa, no obstante, por su ubicación al oeste de la edificación, en horas previas estos espacios se encontraban cubiertos por la sombra de la edificación, lo que se manifestó en una menor temperatura que el resto de espacios con las mismas características físicas, pero con distinta ubicación. No obstante, el beneficio microclimático de esta característica física de los espacios exteriores, es que su efecto se concentra en las proximidades de la edificación, cuya propagación hacia el entorno urbano, se ve limitada por el efecto de calentamiento causado por la configuración de las vialidades y otros espacios edificados cercanos (García- Haro, Arellano, & Roca, 2023).…”
Section: Disposición De Edificaciones Para La Reducción De La Inciden...unclassified
“…Estudios previos han identificado que el efecto de enfriamiento de la vegetación es resultado de la relación entre la calidad, tamaño y configuración de las cubiertas contiguas de vegetación y la intensidad de la isla de calor generada por el medio físico edificado (Rakoto, Deilami, Hurley, Amati, & Sun, 2021;García-Haro, Arellano, & Roca, 2023). Donde entre más compleja y dispersa sea la cubierta de vegetación, menor es su capacidad de contrarrestar la isla de calor urbana.…”
Section: El Papel De La Vegetaciónunclassified
“…Clarifying the underlying mechanisms of the cold island effect in urban parks not only helps enhance their cooling effects but also provides a scientific basis for urban park planning and construction [19]. At present, many studies take several parks in the urban area as samples to analyze the correlation between their characteristics and the intensity of cold islands and then reveal the internal objective laws, which can provide reference for park site selection [20], land cover optimization [21], and vegetation composition renewal [22].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that urban parks, as the most common blue-green landscape combination space in cities, can reduce LST to a certain range 9 , 10 . Researchers assessed LST in 86 urban parks in Barcelona and found that 84 had a cooling effect 11 . Many scholars to date have proposed various indices with a temperature reduction effect.…”
Section: Introductionmentioning
confidence: 99%